Governmental Declassification and the Revision of Recent American History: The Case of the McCarthy Era. - Kouki, Samia (International Journal of the Humanities, 2011)
The McCarthy Era is one of the best-known periods of recent American history. Decades have passed but the memory of what happened is still vivid and the famous question "are you or have you ever been a member of the Communist Party?" still resonates. Few areas of American history have been covered as closely as the domestic Cold War. If one considers McCarthyism as a subject of research there is therefore no telling that the important number of books, scholarly articles, and student theses that have already been written about the subject, have said almost everything about America's fear of communists and its reaction to this fear during the 1940's and 1950's. One is therefore tempted to wonder: what is left to study? What makes further discussion possible? What ought to be mentioned in this context is that more material was indeed added to allow more discussion. The declassification of a top secret document in the mid 1990's, what was called the "Venona Project", opened new possibilities for a new perspective of researching McCarthyism. This new perspective is a revisionist one. Building on this new source of primary documentation, this paper attempts to reconsider the conventional wisdom regarding the infamous witch-hunt episode, and to outline certain limits for reconsideration. Accordingly, the questions addressed in this research are the following: To what extent does this newly available documentation challenge the general understanding of 1940's-50's America? Does the existence of such documents radically change the common interpretation of American domestic anticommunism? What aspects of this infamous episode are to be revised, and can this revision sanction the excesses and the extreme measures undertaken in the "McCarthy Era"?